2021
DOI: 10.3991/ijep.v11i6.24409
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a MOOCs Knowledge Repository System Using a Digital Knowledge Engineering Process to Enhance Digital Entrepreneurs’ Competencies

Abstract: The objectives of this research were as follows: the development of a MOOCs knowledge repository system using a digital knowledge engineering process, and a competency assessment of digital entrepreneurs engaging in a MOOCs knowledge repository system using a digital knowledge engineering process. A total of 30 people were selected as a sampling group (purposive sampling) for this study, these included Small and Medium Enterprises (SMEs) in Bangkok with expertise in Human Performance Technology (HPT), as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The use of MOOCs in technology entrepreneurship courses offers a personalized approach and increases problem solving and multitasking capabilities of learners (Cirulli et al, 2016), while, common experiences and expectations shared between participant students, create business opportunities through knowledge spillovers ( _ Zur, 2020). Digital collaboration, digital workplace and digital awareness are the key DE competencies developed through the usage of MOOCs (Thanachawengsakul and Wannapiroon, 2021). However, there are still challenges to be addressed.…”
Section: Pedagogy and Learningmentioning
confidence: 99%
“…The use of MOOCs in technology entrepreneurship courses offers a personalized approach and increases problem solving and multitasking capabilities of learners (Cirulli et al, 2016), while, common experiences and expectations shared between participant students, create business opportunities through knowledge spillovers ( _ Zur, 2020). Digital collaboration, digital workplace and digital awareness are the key DE competencies developed through the usage of MOOCs (Thanachawengsakul and Wannapiroon, 2021). However, there are still challenges to be addressed.…”
Section: Pedagogy and Learningmentioning
confidence: 99%
“…In this context, it is an important subject in educational modernization to effectively integrate various educational resources to further improve teaching quality. As a platform for centralized storage, management, and utilization of curriculum knowledge, the curriculum knowledge base provides educators with rich teaching resources and students with a wide range of learning paths [1][2][3][4]. However, the construction and application of curriculum knowledge bases currently face many challenges, such as difficulties in data fusion and knowledge reasoning, which require in-depth research on the construction methods of the bases [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…An investigation of the MOOC composition was conducted by performing several studies, as shown in Table 2 [22][23][24][25][26][27][28][29]:…”
mentioning
confidence: 99%